PSYCHOLOGICAL FEATURES OF THE INTERACTION WITH CHARACTERISTIC ACCREDITATION AND REACTION TO FRAUDATION IN DEPARTMENTAL SUPERVISORS - Oros, Valentyna Nikolaevna (Psychological Prospects Journal, 2013)
The article reveals the psychological features of the relationship between the accentuations of the character of depressed teenagers and their reaction to frustration. It has been established that deprivation is a powerful factor in the existence of a correlation relationship between the two above-mentioned phenomena and plays a negative role in the development of the personality of the adolescent in conditions of various types of constraints.